Southeast Asia’s recurring smoke haze crisis : what can be done? - Raman Letchumanan (2015)
The smoke haze crisis in Southeast Asia has come back with a vengeance, threatening the lives and health of millions. No one seems to know how best to deal with it or how long it will last this time.